Prevalence of partial edentulism among young Saudi women of Qassim and their perception of early tooth loss - Almutairy, Amal; Mohan, Minu (International Journal of Dental Research, 2017)
Background: Edentulism and number of remaining teeth per capita are commonly used as main indicators of dental health status in national surveys.Objectives: To determine the level of tooth loss and the most common arch affected, to find the out awareness level of replacement of missing teeth with different prosthetic types and to evaluate the correlation between educational level and tooth loss.Subjects and methods: This was cross-sectional clinical examination, and questionnaire based study, examining the prosthetic status of young females and their level of awareness to replace missing teeth. Using the sample size calculator with the confidence interval of 95% and significance of p<0.05, the sample size was calculated to be 200. The inclusion criteria were female patients visiting Qassim Dental Clinics and primary health care centers, aged between 19-39 years. Data was processed and analyzed through SPSS.Results: The incidences of partial edentulism were 62.5% and the highest level of missing teeth was found among young females who have college and postgraduate degree, which was 52.8%. The restored cases were only16% out of the affected cases. There was a lack of awareness 39.2% to restore missing teeth among study population. The most important cause of loss teeth among the studied population of young females of Qassim was caries 90.4%.Conclusion: The study revealed that young females were concerned about their esthetics than other functions of the masticatory system. This can also be supported with the fact that missing mandible posterior teeth were found to be the most common amongst them. Present study showed that awareness level and motivation were significantly low to restore missing teeth. It also revealed that educational status was not the only predictor of health outcomes.